2003
DOI: 10.1159/000068036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Acute Dose of <i>L-</i>Arginine during Coronary Angiography in Patients with Chronic Renal Failure

Abstract: Background: Contrast media (CM) are nephrotoxic and might further worsen renal function in patients with chronic renal failure. L-Arginine, the substrate of nitric oxide, protects kidney function and may improve endothelial function in patients with coronary artery disease. Hypothesis: Acute administration of L-arginine in a subset of patients with combined coronary artery disease and impaired kidney function during coronary angiography might prevent superimposed acute renal failure. Methods: A double-blind st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
0
17
0
2
Order By: Relevance
“…[136][137][138][139] L-arginine supplementation therapy as anti-atherosclerotic approach was supported by numerous studies, 50,[140][141][142][143][144][145] but is recently challenged by increasing the number of other studies showing no such effect or no sustained effect on endothelial function. 50,[145][146][147][148][149] Some studies even showed a harmful effect on atherosclerotic lesion formation 150 in animal models, such as in ApoE -/-/iNOS -/-double knockout mice which are treated chronically with L-arginine supplementation. An increase in production of superoxide anion in atherosclerotic rabbit aortas treated with L-arginine has been recently described.…”
Section: An Endogenous Inhibitor Of Enos: Asymmetric Dimethylargininementioning
confidence: 99%
“…[136][137][138][139] L-arginine supplementation therapy as anti-atherosclerotic approach was supported by numerous studies, 50,[140][141][142][143][144][145] but is recently challenged by increasing the number of other studies showing no such effect or no sustained effect on endothelial function. 50,[145][146][147][148][149] Some studies even showed a harmful effect on atherosclerotic lesion formation 150 in animal models, such as in ApoE -/-/iNOS -/-double knockout mice which are treated chronically with L-arginine supplementation. An increase in production of superoxide anion in atherosclerotic rabbit aortas treated with L-arginine has been recently described.…”
Section: An Endogenous Inhibitor Of Enos: Asymmetric Dimethylargininementioning
confidence: 99%
“…Following these early studies, numerous studies with supplemental Larginine therapy have been conducted in animal models and in humans; however, no consistent results can be achieved [24••]. In recent years, there has been an increasing number of studies showing either no effect or no sustained effects on endothelial function by L-arginine supplementation [6,[25][26][27][28][29][30]. Harmful effects on atherosclerotic lesion formation in ApoE/iNOS double-knockout mice have been reported [31].…”
Section: Controversy Of L-arginine Supplemental Therapy In Atherosclementioning
confidence: 99%
“…Intravenous hydration with 0.9% SS) 0.9% SS 1 mL/kg/h, 12 hours before and 12 hours after the procedure Several randomized studies and metaanalyses 30,[32][33][34] 0.9% SS is superior to 0.45% SS 23,32 Sodium bicarbonate (154 mEq/L) NaHCO3 3 mL/kg/h, 1 hour before the procedure and 1 mL/kg/h, 6 hours after the procedure Several randomized studies and meta-analyses 32,[49][50][51][52][53][54] Dilute 154 mL of 8.4% sodium bicarbonate in 846 mL of distilled water for obtaining the solution Type of contrast medium Low-osmolality or iso-osmolality contrast medium Some randomized studies and a few meta-analyses [26][27][28] The literature is still controversial whether isoosmolality contrast medium is superior to low-osmolality contrast medium 29 N-acetyl cysteine 600 mg, orally, 12/12 hours, 24 hours before and after the procedure Still controversial 54,55 Large ongoing multicenter study 56 …”
Section: Most Used Methods Evidence Level Commentsmentioning
confidence: 99%
“…[41][42][43][44] Other vasodilating drugs that showed no benefit as compared with placebo in preventing CN were the atrial natriuretic peptide, 45 endothelin antagonists, 46 prostaglandin E 1 , 47 ACE inhibitors 2,48 , and L-arginine. 49 In reality, endothelin antagonists not only did not benefit but also increased the risk of CN for users. 46 Prophylactic hemofiltration has been associated with a reduction in the adverse events related to CN in high risk patients.…”
Section: Saline Solutionmentioning
confidence: 99%